MARKETING STRATEGY FOR TAMAN HUTAN RAYA IR. H. DJUANDA, BANDUNG - Arditama Febrianza, Muhammad
Tourism is a multidimensional and multidisciplinary subject. Many other disciplines are mutually supportive and complementary in the process of tourism development, one of which is the marketing field. Basically, is the tourism marketing efforts to attract more tourists come, stay longer and spend more money in a travel destination. Ir. H. Djuanda Forest Park as one of the assets for tourism in the city of Bandung, is assumed not managed optimally. The development of this region tend to be allowed to flow. Not that this Ir. H. Djuanda Forest Park management does not have a plan, but implementation of the existing plan does not appear is implemented optimally. The purpose of this study is the formulation of marketing strategies that can be applied at Ir. H. Djuanda Forest Park. The objective of this study was to determine the visitor’s characteristics, identify the obstacles encountered in the management as well as the alternative solutions offered and the formulation of marketing strategies in the management of Ir. H. Djuanda Forest Park. SWOT (Strength, Weakness, Opportunity, Threat) Analysis is used to map the strengths and weaknesses of internal and external sides of the region and formulate alternative solutions to management constraints, the implementation of marketing mix 7 P (7P (Product, Price, Place, Promotion, Physical Evidence, People, Process) used to formulate the regional marketing strategy. Data collecting technique used are distributing questionnaires, field observations, interviews and document studies. The findings of the study stated that the Ir. H. Djuanda Forest Park has two types of tourist attractions consisting of natural attractions in the form of Curug Dago, Curug Maribaya and Pine Forests, as well as historical tourist attractions in the form of Japan Cave, Netherland Cave, Djuanda Museum, Ir. H. Juanda Statue and King of Thailand Inscription Stone. Tourists / consumers profile and characteristics who visit the Region Forest Park Ir. H. Djuanda is dominated by local tourists with a percentage of 100%. Originating from the area of Bandung, Cimahi, Lembang, Garut, Bekasi, Jakarta, Tangerang, Bali and Medan. Traveller dominated by men aged between 12-30 years. Tourists who come predominantly have eduactional background from SD - SMP - SMA - University. 5 Average earnings travelers Rp. 1000.000 per month. Traveler characteristics dominant in groups, by mode of transport using motorcycles and private cars, traveling time in the morning on weekends, with the majority of tourists spend 30 minutes - 1 hour to reach the area of Ir. H. Djuanda Forest Park. Most of travelers assume that the Ir. H. Djuanda forest park is a tourist area that has natural attractions and historical attractions, the majority of tourists obtain travel information from colleagues / family (word of mouth) as well as social media. The majority of tourists are visiting for the first time traveled with a duration of 1-3 hours. From the total respondents, there were 7 tourists choose to stay at the homes of relatives / siblings and 3 tourists choose to stay at the hotel, the rest chose to return to their home area. Characteristics of tourists coming motivation is for recreation in the area of Ir. H. Djuanda Forest Park with main activity is walking - street. Costs incurred most travelers spend less than Rp. 50,000. After making the formulation of a marketing strategy based on SWOT analysis (Strength, Weakness, Opportunity, Threat), there are 8 suggestions recommended, they are arrangement of the region, the addition of support facilities, improved accessibility, standardization of prices, the integration of public transport, digital promotion, human resource development planning and realization of the travel package.